2023
DOI: 10.1002/clc.24077
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with oral anticoagulant prescription status among patients with a new diagnosis of atrial fibrillation

Abstract: BackgroundAtrial fibrillation (AF) is the most common sustained arrhythmia in adults and increases stroke risk. Treatment with oral anticoagulants (OACs) may reduce this risk however many patients do not receive OAC therapy. This study aimed to use electronic health record data to identify newly diagnosed AF patients at high risk for stroke and not anticoagulated as well as factors associated with OAC prescription.HypothesisTimely prescription of OACs among patients with newly diagnosed AF is poor.MethodsWe pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 13 publications
(28 reference statements)
0
4
0
Order By: Relevance
“…3 In the authors' study, the use of antiarrhythmic drugs was associated with a lower rate of OAC prescription, which is inconsistent with other previous studies. 1 This is probably due to the old concept: rhythm control versus rate control, in which rhythm control is sufficient to prevent stroke without anticoagulation. 2 Again, the observation period may be relatively too old to apply their findings to the current era.…”
Section: Factors Associated With Prescription Of Oral Anticoagulants ...mentioning
confidence: 99%
See 3 more Smart Citations
“…3 In the authors' study, the use of antiarrhythmic drugs was associated with a lower rate of OAC prescription, which is inconsistent with other previous studies. 1 This is probably due to the old concept: rhythm control versus rate control, in which rhythm control is sufficient to prevent stroke without anticoagulation. 2 Again, the observation period may be relatively too old to apply their findings to the current era.…”
Section: Factors Associated With Prescription Of Oral Anticoagulants ...mentioning
confidence: 99%
“…Appropriate prescription of oral anticoagulants (OACs) for patients with atrial fibrillation (AF) and high stroke risk is of great importance. Manning 1 and colleagues evaluated the prevalence of OAC prescription within 6 months after the first diagnosis of AF in patients at high stroke risk during the observation period between 2013 and 2018. 1 They demonstrated that most newly diagnosed AF patients at high stroke risk did not receive OAC prescription within the first 6 months after the diagnosis.…”
mentioning
confidence: 99%
See 2 more Smart Citations